The Increasing the Efficiency of Material Recovery Facility through Source Separation of Residential Solid Waste, the case of Duhok city - Kochar, Qaidar (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
This study investigates the separation of residential solid waste at the household level in Dohuk city and its potential impact on the capacity of material recovery facility (MRF) in Kwashe fabric. With a rough daily capacity of 500 tons of municipal solid waste (MSW), this facility is currently able to process only 50% of this quantity – manually using hired laborers. The unprocessed waste is usually disposed of in a nearby open dumpsite. In addition, the limited capacity of Kwashe facility is further hampered by the need for more labor force, which makes the sorting process not be cost-effective and of health hazards to the workers. This study's results, which targeted 26 households in two economically different neighborhoods (Baroshke and Gre-sor), reveal that household waste is not separated, and the proportion of wet waste is much higher than the dry waste (65% vs. 35%). This indicates that this finding has no co-relation with the residents' living conditions level but with the cultural habits – eating freshly cooked food and cooking more than they need. They also reveal that dry wastes such as batteries and dying materials contain Cadmium, a chemical that contaminates recyclable materials. Hence, one of the effective strategies to increase Kwashe facility's capacity is to separate the residential solid waste at the source, as the wet waste can be directly converted into compost, which is 65% in average of the total residential waste. In contrast, dry waste can be separated and recycled in a more cost-effect manner with fewer health risks to the workers and better quality of the outputs.